The Feasibility of Kopikaya Learning Media (Smart Box of Cultural Diversity) to Improve the Learning Outcomes of Grade V Elementary School Students - Putri, Farah Fauziyah Dila; Fatimah, Iis Daniati (Universitas Nusantara PGRI Kediri, 2025)
Education is a conscious and planned effort to create an active and conducive learning process so that students are able to develop their potential optimally. One important instrument in education is the curriculum, including the Independent Curriculum which encourages the use of technology and learning innovation. However, observations at SDN Baturetno 1 show that learning is still conventional and does not utilize innovative media, resulting in low learning outcomes, especially in the material